Women, Islamic Boarding Schools, and Communications: Interpersonal Approach of Islamic Boarding School Leadership - D.I. Ansusa Putra; Sandi Maspika; Umdatul Maghfiroh (INNOVATIO: Journal for Religious Innovation Studies, 2021)
Abstract: The reality of pesantren that is identical with Kyai and masculinity is caused by a gender bias towards women's leadership. Women are deemed incapable of being communication leaders to mobilize Islamic Boarding school activities. Contrary to that, this article aims to prove that women's leadership communication patterns can positively impact pesantren activities, even though a female leader faces several problems at the Islamic boarding school. This article uses a descriptive qualitative method based on the leadership observation of Dra. Tiaman at the Ummul Masakin Islamic Boarding School, Jambi. This study also uses in-depth interview techniques and data documentation related to the themes: 1) Leadership, 2) Communication, and 3) Islamic boarding schools. The article reveals that the leadership of women in Islamic boarding schools can positively impact the development of the students' personality and the activities of the Islamic Boarding School because interpersonal communication patterns dominate the communication patterns that are built. Women have the power of wisdom to drive positive things and minimize negative things, such as conflicts or disharmony problems, especially in Islamic educational institutions such as Islamic boarding schools. Abstrak: Realitas pesantren yang identik dengan kiyai dan maskulinitas disebabkan oleh bias gender terhadap kepemimpinan perempuan. Perempuan dianggap tidak cakap menjadi communication leader untuk menggerakkan aktifitas kepesantrenan. Bertentangan dengan itu, artikel ini bertujuan untuk membuktikan bahwa pola komunikasi kepemimpinan perempuan mampu memberikan dampak yang positif terhadap aktifitas pesantren, meskipun terdapat berberapa problematika yang dihadapi oleh seorang pemimpin perempuan di pondok pesantren. Artikel ini menggunakan metode kualitatif deskriptif dari observasi kepemimpinan Dra. Tiaman di pondok pesantren Ummul Masakin, Jambi. Penelitian ini juga menggunakan teknik wawancara mendalam dan dokumentasi data yang berkaitan dengan tema: 1) Kepemimpinan, 2) Komunikasi, dan 3) Pondok pesantren. Artikel menyimpulkan bahwa Kepemimpinan perempuan di pondok pesantren dapat memberikan dampak positif kepada pengembangan kepribadian santri dan aktifitas kepesantrenan karena pola komunikasi yang dibangun yang didominasi oleh pola komunikasi interpersonal. Hal ini disebabkan perempuan memiliki kekuatan wisdom yang mampu menggerakkan hal positif dan meminimalisir hal negative, seperti konflik atau problem disharmoni khususnya pada lembaga pendidikan Islam seperti pesantren. Kata-kata kunci: Pola Komunikasi, Pemimpin Perempuan, Pondok Pesantren